Zum Verhältnis von Heimatverlust und Neubeginn in frühen Romanen über Flucht und Vertreibung - Janzen, Frauke (Studia Germanica Posnaniensia, 2013)
This article looks at early West German novels that depict flight and expulsion of Germans after World War II. It is already in the 1950s that German literature takes up on East German home loss; especially authors originating from the Eastern parts make flight and expulsion subject of their works. How then do those novels reflect the radical change – as a beginning, as an ending? What did 1945 mean to those Germans who had to flee their homes beyond Oder and Neisse? – The end of German culture in Eastern Europe? The final surrender of their homelands? And how could the expellees restart their life in the Western parts? The article interlaces these questions with the texts’ narrative time structures. Most of the novels focus on the process of flight and expulsion and skip the arrival and integration in the West. Thus, the novels attest the uncertainty inherent in the new beginning. The article argues that the authors do not narrate the ending of the transition because in the 1950s for them it has not ended yet. It investigates three representative novels: Engel, Menschen und Dämonen (1951) by Hanna Stephan, Die schlesische Barmherzigkeit (1950) by Ruth Hoffmann and Ein Abschied (1951) by Karl Borree.